Trifluoromethylsulfide Anion: Generation and Reaction with Pentafluoropyridine - Wojciech Dmowski; Alois Haas (CHIMIA)
The anion F3CS⊖, generated from thiocarbonyl difluoride 1 and alkali metal fluorides, reacts with pentafluoropyridine 2 to give high yield of 2,3,5,6-tetrafluoro-4-trifluoromethylthiopyridine 3.